2017
DOI: 10.2139/ssrn.2906336
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric Price Volatility Interaction between U.S. Food and Energy Markets

Abstract: Links between agricultural commodity and energy prices have become more complex with increased ethanol production. The concerns are whether the new corn-ethanol links lead to volatility-spillover effects between food and energy prices and different data-frequencies is the reason for previous inconsistent results. We investigate the asymmetric volatility-spillover effects between U.S. feedstock and biofuel prices, using an asymmetric BEKK-multivariate-GARCH approach, with daily, weekly, and monthly futures-pric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 31 publications
1
29
0
1
Order By: Relevance
“…These outcomes suggest that the future prices can be used for risk management purpose. Saghaian et al (2018) also confirmed the volatility spillover between the corn and ethanol markets. The authors showed that the relationship is bidirectional.…”
Section: Literature Reviewsupporting
confidence: 58%
“…These outcomes suggest that the future prices can be used for risk management purpose. Saghaian et al (2018) also confirmed the volatility spillover between the corn and ethanol markets. The authors showed that the relationship is bidirectional.…”
Section: Literature Reviewsupporting
confidence: 58%
“…Similar findings are confirmed by Merkusheva and Rapsomanikis (2014) who consider corn as quasi-fixed input in the production of ethanol, and thus its price can influence the price of ethanol. Saghaian et al (2018) also show that corn-ethanol links exist and corn and ethanol price volatility influence each other. Given a change in the corn price, ethanol prices respond to a change in corn prices fast and adjust to a change by 22 percent each month.…”
Section: Methodsmentioning
confidence: 75%
“…The study suggests that oil prices are more likely to influence corn and soybean prices in the long term than in the short term. Saghaian et al [29] find evidence of volatility transmission between oil, corn, and ethanol prices using the BEKK (Baba, Engle, Kraft, and Kroner)-multivariate generalized autoregressive conditionally heteroskedastic (BEKK-MGARCH) approach [30]. Yahya, Oglend, and Dahl [31] found that soybean oil, soybeans, and corn demonstrated the strongest dependence on crude oil returns in the post-2006 period, whereas the parameters of dependencies were low in the pre-2006 subsample.…”
Section: Introductionmentioning
confidence: 99%